Massive pulmonary thromboembolism combined with transient thyrotoxicosis in an 18 year old girl - Tong-Yoon Kim; Sang-Hyun Ihm; Ji Woong Roh; Sungmin Lim; Chan-Seok Park; Hee-Yeol Kim (BMC, 2020)
Abstract Background Pulmonary thromboembolism (PTE) is thought to usually stem from deep vein thrombosis (DVT). However, evidence of DVT could not be found in many cases. Furthermore, transient thyrotoxicosis is a rare but potentially life-threatening emergency involving a systemic hypercoagulable state. We report on an 18 year-old-girl with transient thyrotoxicosis with massive PTE without DVT. Case presentation An 18-year-old girl was admitted to the hospital with syncope. Patient had no history of trauma, any known underlying disease or oral contraceptives use. Chest computed tomography (CT) showed massive PTE in both central pulmonary arteries and diffuse goiter. However, a low extremity Doppler sonogram did not detect DVT. To manage the PTE, we administered low molecular weight heparin. On the other hands, thyroid function test indicated a state of thyrotoxicosis. In addition, patient had a partial protein S deficiency but no other immunologic abnormality. Therefore, the patient was diagnosed with massive PTE, thyrotoxicosis, and partial protein S deficiency. Patient was discharged with oral warfarin and methimazole. A follow-up echocardiogram obtained 3 months after anticoagulation therapy demonstrated normal dimensions and systolic function. After thyrotoxicosis was treated with methimazole for a month, a euthyroid state was achieved and the goiter decreased to a normal size. The methimazole was gradually tapered off and stopped at 4 months. At a 6-month follow up visit, PTE and pulmonary hypertension had disappeared but the patient still had a partial protein S deficiency. We decided to stop all medication with careful monitoring. During a 4-year follow-up period after the episode, she was asymptomatic without any evidence of recurrent systemic thromboembolism or hyperthyroidism. Conclusions Early recognition and appropriate treatment of PTE combined with transient thyrotoxicosis were vital to preventing other complications.